1984
DOI: 10.1172/jci111578
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation of platelet thrombospondin with plasminogen. Modulation of activation by tissue activator.

Abstract: A bstract. Thrombospondin (TSP), a multifunctional a-granule glycoprotein of platelets, binds fibrinogen, fibronectin, heparin, and histidine-rich glycoprotein and thus may play an important role in regulating thrombotic influences at vessel surfaces. In this study we have demonstrated that purified human platelet TSP formed a complex with purified human plasminogen (Plg). Complex formation was detected by rocket immunoelectrophoresis of mixtures of the purified radiolabeled proteins. Significant complex forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
1
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 35 publications
4
96
1
1
Order By: Relevance
“…This hypothesis is supported by the results of recent studies that demonstrated that platelet thrombospondin combines with plasminogen and inhibits its activation. 28 The reason that bleeding was not induced by t-PA in a concentration that was able to produce approximately 35% lysis is less clear. It is possible that fibrin present in the hemostatic plug is more resistant to lysis by t-PA than fibrin in thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the results of recent studies that demonstrated that platelet thrombospondin combines with plasminogen and inhibits its activation. 28 The reason that bleeding was not induced by t-PA in a concentration that was able to produce approximately 35% lysis is less clear. It is possible that fibrin present in the hemostatic plug is more resistant to lysis by t-PA than fibrin in thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…Supramolecular assembly, covalent modifications, and limited proteolysis are known to modulate integrin binding activities of specific matrix proteins (reviewed in (Silverstein et al, 1984;Davis et al, 2000)). Some integrin ligands may also be subject to conformational regulation of activity similar to that described for their receptors.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 After experimental arterial injury, TSP-1 mRNA expression is upregulated within hours. 5 Functionally, TSP-1 has been shown to (1) promote cell adhesion, proliferation, and migration, 2,6 (2) modulate angiogenesis, 7,8 (3) regulate plasmin production, 9 and (4) activate transforming growth factor (TGF)-␤1. 9,10 TSP-2 is similar to TSP-1 in terms of its molecular architecture, but it shows a different pattern of expression in developing organisms.…”
mentioning
confidence: 99%